Evaluation of Various Carbonated Soft Drinks to Assess their Effects on Human Health - Aamir Ali; Muhammad Ayaz Afridi; Muhammad Mansoor; Waqas Chohan; Aasir Ali; Hafiz Muhammad Zaheer Afzal (Scientific Inquiry and Review, 2022)
Sugar, citric acid, phosphoric acid, and caffeine are extensively present in soft drinks. The high concentrations of these elements have harmful effects on human health. A series of nine carbonated drinks namely Pepsi, Mountain Dew, 7-up, Mirinda, Coca cola, Sprite, Fanta, Amrat cola, and Amrat lemon were collected from the open market of Peshawar, Pakistan. Various physicochemical parameters were measured to evaluate the quality of the collected drinks. Brix (Total dissolved solids) were found to be 11.40, 11.90, 10.70, 12.90, 10.37, 10.0, 13.00, 10.6, and 10.20% in Pepsi, Mountain Dew, 7-up, Mirinda, Coca-cola, Sprite, Fanta, Amrat cola, and Amrat lemon, respectively. CO2 gas volume (G. V) was found to be 3.60, 3.20, 3.70, 1.80, 3.80, 3.80, 1.80, 3.80, and 3.70 G.V in Pepsi, Mountain Dew, 7-up, Mirinda, Coca-cola Sprite Fanta, Amrat cola, and Amrat lemon, respectively. Caffeine was found only in Pepsi, Coca cola, Amrat cola, and Mountain Dew, having a concentration of 103, 105, 109, and 146 mg/L, respectively. Pepsi, Coca cola, and Amrat cola were free of citric acid. The citric acid amounts were 1337.6, 1459.2, 1816.32, 1196.8, 1664, and 1216 mg/L in Mountain Dew, 7-up, Mirinda, Sprite, Fanta, and Amrat lemon, respectively. Phosphoric acid was found only in Pepsi, Coca cola, and Amrat cola, in the amounts of 583.1, 490, and 588 mg/L, respectively. It is concluded that the frequent use of carbonated soft drinks (CSD) could cause serious health damage.